The Polarized Redistribution of the Contractile Vacuole to the Rear of the Cell is Critical for Streaming and is Regulated by PI(4,5)P2-Mediated Exocytosis - Fadil, Sana A.; Janetopoulos, Chris (Frontiers in Cell and Developmental Biology, 2022)
Dictyostelium discoideum amoebae align in a head to tail manner during the process of streaming during fruiting body formation. The chemoattractant cAMP is the chemoattractant regulating cell migration during this process and is released from the rear of cells. The process by which this cAMP release occurs has alluded investigators for many decades, but new findings suggest that this release can occur through expulsion during contractile vacuole (CV) ejection. The CV is an organelle that performs several functions inside the cell including the regulation of osmolarity, and discharges its content via exocytosis. The CV localizes to the rear of the cell and appears to be part of the polarity network, with the localization under the influence of the plasma membrane (PM) lipids, including the phosphoinositides (PIs), among those is PI(4,5)P2, the most abundant PI on the PM. Research on D. discoideum and neutrophils have shown that PI(4,5)P2 is enriched at the rear of migrating cells. In several systems, it has been shown that the essential regulator of exocytosis is through the exocyst complex, mediated in part by PI(4,5)P2-binding. This review features the role of the CV complex in D. discoideum signaling with a focus on the role of PI(4,5)P2 in regulating CV exocytosis and localization. Many of the regulators of these processes are conserved during evolution, so the mechanisms controlling exocytosis and membrane trafficking in D. discoideum and mammalian cells will be discussed, highlighting their important functions in membrane trafficking and signaling in health and disease.